Ambulatory cleft lip surgery in a developing country (2015)
Background: Ambulatory cleft lip surgery has been practiced extensively in many developed countries, however cleft lip repair in most developing countries involve patient hospitalization of varying duration. Driven bythe recent acute shortage of pediatric bed space in our hospital, an increasing number of cleft lip surgeries are being performed on out-patient basis. The aim of this study was to report our experience with ambulatory cleft lip surgery at the University College Hospital, Ibadan. Methods: A retrospective review of Cleft lip Surgeries performed between February 2007 and January 2010 was done. Data of patients who had cleft lip surgery was retrieved from our Smile Train data base, the operating room surgery records and the Nurses' admission/discharge records on ail the wards on which the patients were either received or admitted. Information obtained included the demographic characteristics of the patients, complications reported, length of stay (LOS) for in-patients and the need for re-admission before the first follow-up clinic appointment among the two groups. Results: Eighty three patients were identified but complete data was obtained for forty patients. (Retrieval rate of 48%) The ambulatory group comprised of 15 patients while- the in-patient group had 25 patients. The mean patient age was 5.7years in the ambulatory and 9.7 years in the in-patient group. Both groups were homogenous for other parameters. None of the patients in the ambulatory group was re-admitted for any post-operative complication while only one patient in the in-patient group had a post-operative complication necessitating prolonged hospitalization. Conclusion: Ambulatory cleft lip surgery was found to be safe in our practice with comparable patient outcome to the in-patient group. It is anticipated that this may assume increasing prominence in the scope of cleft lip management in many more centers in the developing world.